Keragaan Kelas Kemampuan Kelompok Tani Sayuran di Kota Banjarbaru - Mariani Mariani; Usamah Hanafie; Harisa Novita Yuliani (AGRIDES: Jurnal Agribisnis Perdesaan, 2011)
This research is purposed to learn the vegetables farmers group’s ability class performance in Banjarbaru city according to the good vegetables cultivation guidance and farmer group ability appraisal guidance. it is also aimed to learn about the influencing farmer group performance class factor and also about the problem which is handled by vegetables farmers group in Banjarbaru. Based on the result of data counting and analysis, it is concluded that 1)The vegetables farmers group’s ability class performance in Banjarbaru shows that all farmers group ability on vegetables cultivation is not classified as a firstrate, whereas the ability class is classified as advance (80%) and high (20%). 2) The influencing factor the vegetables farmers group’s ability in Banjarbaru consist of: Cultivation factor and farmers group ability movements. 3) Farmers group’s problem is the limitation of financial capital, hard to have a meeting, limited field, weather condition, less of production facilities, no note and documentation of farmering, pesticides are not according to SOP, not yet use a tested and legal bio-pesticides, and also there is no clear history of filed for one year.